PERBANDINGAN PENGARUH MODEL PEMBELAJARAN TIME TOKEN DENGAN THINK TALK WRITE TERHADAP KETERAMPILAN SOSIAL PESERTA DIDIK DALAM PEMBELAJARAN IPS DI SMPN 10 PALEMBANG - Hamidah; Yulia Djahir; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
This study discusses the comparative influence learning models of learning Time Token with Think Talk Write to the social skills of students in learning social studies in junior high school N 10 Palembang. The formulation of the research problem, namely "Is there a difference influences learning models of learning Time Token with Think Talk Write to the social skills of students in social studies learning". This research is a comparative studywith a completely rendomized design method. The populastion in the study were all class VIII SMP Negeri 10 Palembang. Sampling using random cluster sampling, obtained VIII.11 class (experimen 1) and class VIII.12 (experiment 2) with the number 38 and 40 learners. Data collection technique used observation. The results of the analysis of social skills of observational data on the social skill aquired experiment-1 value of 97.4%, an experiment-2 obtained a value of 84.1%. The calculation results of hypothesis testing using t test obtained tcount≥ttable = 10.75 ≥ 1.985. This means that there are differences in the influence of the model TimeToken with Think Talk Write to social skills The constraints study, students have the opportunity to speak is not used efficiently, the difficulty of arranging the learners in doing stage Think, but to convince the students to dare argue and set the time the second constraint can be controlled.